CMOS-MEMS Oscillator Architecture and Phase Noise: A Mini-Review - Li, Ming-Huang (Frontiers in Mechanical Engineering, 2022)
Over the past two decades, the advancement in microelectromechanical systems (MEMS) has been making headway in the development of miniaturized mechanical structures with integrated electronics. By adopting the existing layer in the complementary metal-oxide-semiconductor (CMOS) fabrication platform, the so-called “CMOS-MEMS” technology offers an intrinsic circuit-MEMS integration scheme, paving a way to realize monolithic micromechanical oscillators for frequency control and sensing applications. To enhance the functionality of the oscillator, it is cardinal to understand the secrets behind the resonator and circuit design techniques to generate high spectral purity signals. As the oscillator characteristics heavily depend on the resonator’s motional parameters, the circuit configuration is determined in accordance with the post-CMOS processing technology and the mode shape of the resonator. In this mini-review, we attempt to summarize and appraise studies related to the design and optimization of CMOS-MEMS oscillators and to give directions for future researchers in terms of phase noise.